Knockdown of MDM2 in HepG2 Cell Line: A Step Towards Understanding the Relation Between miRNA590-3p and its Downstream Target Gene, MDM2, in Hepatocellular Carcinoma - Mahmoud, Jihad (AUC Knowledge Fountain, 2022)
Background: miRNA 590-3p is a small non-coding RNA that has previously been associated with the occurrence and progression of several cancer types. Its expression pattern and biological role in Hepatocellular carcinoma (HCC), however, remain controversial. Interestingly, a previous study in our lab revealed a tumor suppressing activity of miR-590-3p in HCC and identified the MDM2 gene as the miR-590-3p target gene. Aim: The current study aimed to knock down the expression of MDM2 in HepG2 cells to understand how the inhibition of MDM2, as a validated downstream target of miR-590-3p, would affect different functional pathways in HCC. In addition, we aimed to identify further downstream targets in the “mir-590-3p-MDM2” pathway and understand their role in the development of HCC. Methods: RNAi-mediated knockdown was used to inhibit mRNA and protein levels of MDM2. Clonogenic cell survival assay was utilized to assess HepG2 cell proliferation, while transwell assay was carried out to evaluate the migratory behavior of these cells. miR-590-3p (mimics and NC) transfected HepG2 cells were used to assess the effect of miR-590-3p overexpression on target genes. In silico analysis was employed to identify further downstream targets in the “mir-590-3p-MDM2” pathway. Potential target genes predicted by bioinformatics tools were subjected to RT-qPCR analysis. Results: The transient knockdown of MDM2 in the HepG2 cells had a silencing effect up to 80% at mRNA level and almost 70% at protein level. In clonogenic cell survival assay and transwell assays, MDM2 gene silencing was shown to inhibit cell proliferative and migratory behavior of HepG2 cells. Gene expression analysis revealed that this miRNA functions, at least in part, by influencing the expression of genes that regulate EMT progression, which was also downregulated following MDM2 knockdown in HepG2 cells. Additionally, FOXO3 was identified as a novel target in the miR-590-3p/MDM2 pathway. Conclusion: Our results not only reveal a crucial role for MDM2 in the regulatory mechanism of EMT in HCC but also demonstrate novel targets for miR-590-3p in HCC. Moreover, these results shed light on the important role of the miR-590-3p/MDM2 pathway in HCC.